Biometria ocular na espécie Cebus apella - Estanislau, Cristiane de Abreu [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The aim of this study was to determine the ocular dimensions of capuchin monkeys using ultrasound A and keratometry, determining the refractive power of the IOL formulas employing third and fourth generation. Were used 18 animals (36 eyes) of the species Cebus apella. The calculation of intraocular lens was performed using the Holladay IOL Consultant ® and EyeCalculator ® 6.0 software. Holladay 2, Hoffer Q, and Haigis formulas were employed to do the calculus and determin lenses with an average refractive power of 29.43 D; 31.25 D and 46.71 D, respectively. No statistical difference was observed between the lens dioptric values calculated by formulas Holladay 2 and Haigis; however, we could see statistical difference between groups when the the formula Hoffer Q was applied, resulting in more powerful lenses. The reviews of ocular biometric parameters and the lens power calculated by the same formula showed neither significant differences between males and females, or between the right and left eyes of each animal

O objetivo deste trabalho foi determinar as dimensões oculares dos macacos-prego por meio de ultrassonografia modo-A e ceratometria, e determinar o poder dióptrico da lente intraocular empregando-se fórmulas de terceira e quarta geração. Foram utilizados 18 animais (36 olhos) da espécie Cebus apella. O cálculo da lente intraocular foi realizado utilizando-se o software Holladay IOL Consultant® e EyeCalculator 6.0®. As fórmulas empregadas para o cálculo foram Holladay 2, Haigis e Hoffer Q que possibilitaram prever lentes com poder dióptrico médio de 29,43 D; 31,25D e 46,71D, respectivamente. Não foi observado diferença estatística entre os valores dióptricos das lentes calculadas pelas fórmulas Holladay 2 e Haigis; no entanto, com a aplicação da fórmula Hoffer Q observou-se diferença estatística, determinando lentes mais potentes. Considerando os parâmetros biométricos oculares avaliados, e o poder dióptrico calculado por uma mesma fórmula não há diferenças significativas entre machos e fêmeas, e lateralidade dos olhos para um mesmo animal
Ocular biometry of Cebus apella
Keywords: Macaco Prego Pesquisa; Cebus apella; Lentes intra-oculares; Olhos - Cirurgia; Biometria; Modelos animais em pesquisa; Animal models in research